2014
DOI: 10.1371/journal.pone.0106879
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Epilepsy: A Study of Brazilian Adolescents

Abstract: ObjectiveOur objectives were: to assess the QOL of Brazilian adolescents with epilepsy with a specific QOL assessment tool; to compare the adolescents with epilepsy and healthy adolescents using a generic QOL assessment tool; to correlate the 2 different QOL assessment tools (the generic and the epilepsy-specific); and to correlate QOL scores of the adolescents with epilepsy obtained by both tools with physical, psychological and social variables of the disease.MethodsFifty subjects (case group) attending the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 15 publications
1
7
5
Order By: Relevance
“…In this study, demographic factors linked to the QoL in adolescent patients with an epilepsy diagnosis were analyzed, obtaining similar results to previous studies through the QoLIE-48 questionnaire (Table 3) [11][12][13][14][15][16][17][18][19][20] .…”
Section: Discussionsupporting
confidence: 75%
“…In this study, demographic factors linked to the QoL in adolescent patients with an epilepsy diagnosis were analyzed, obtaining similar results to previous studies through the QoLIE-48 questionnaire (Table 3) [11][12][13][14][15][16][17][18][19][20] .…”
Section: Discussionsupporting
confidence: 75%
“…On this ndings quality of life on physical domain mean ranked relatively higher (58.6) in the WHOQOL-BRIEF scaled scores when compared to the social (53.3), psychological (50.25%) and environmental domain mean (48.75), however the nding of this study on physical domain mean was lower than studies done in Brazil (72.76) (11). This might be due to the management approach for epilepsy in this hospital might not be focus on adopting a holistic approach that also incorporates their psychological, social and environmental needs rather than focusing only seizure control.…”
Section: Discussioncontrasting
confidence: 67%
“…This may be due to research done in Mekelle city was used QOLIE-31 tool that was focus on the seizure worry, wellbeing, energy/fatigue, cognitive functioning and medication effect. This nding also lower than studies done in Brazil (68.73) (11) and Malaysia (68.9) (8). This difference might be due to those countries had better quality of health services, good socioeconomic status of the population than Africa population.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…[ 53 ] Better QOL was observed in seizure-free PWE who had good perception of seizure control and not experienced seizures in public places. [ 54 ] Improvement in QOL was observed in PWE who were seizure free for the last 12 weeks of 28-week clinical trial on antiepileptic drugs. [ 55 ] In our study, higher mean total QOL and subscale scores were observed in seizure-free PWE when compared to seizure-frequent PWE.…”
Section: Discussionmentioning
confidence: 99%